The role of indicators in development cooperation: an overview study with a special focus on the use of key and standard indicators - Sarah Holzapfel (Deutsches Institut für Entwicklungspolitik (DIE), 2014)
With more and more emphasis being placed on results and the clamour for transparency and accountability growing ever more vocal, indicators are becoming increasingly important in development cooperation. By measuring changes and providing contextual information, they help to plan and implement development interventions or strategies, to monitor and evaluate, and also to report on development results. However, indicators are not always easy to use. The fact is that they come with many limitations and potential adverse effects. These challenges and risks differ among the three organisational levels suited to results-based management and reporting systems: agency, country and programme or project level. Against this background, this study analyses the use of indicators at the three organisational levels and makes recommendations on how they can best be used and how the associated risks can be mitigated. Special emphasis is placed on agency-level performance measurement systems, since evidence on them is scarce. With the aid of a literature review and a number of semi-structured interviews, the study compares the experiences of twelve selected donor agencies with key and standard indicators for reporting development results at agency level.
Keywords: 330; Wirksamkeit und Evaluierung